2020
DOI: 10.3389/fphar.2020.00250
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Fibroblast Growth Factor 10 Signaling in Duodenal Atresia

Abstract: Introduction: Duodenal atresia (DA) is a congenital bowel obstruction requiring major surgery in the first week of life. Three morphological phenotypes are described, reflecting increasing degrees of obstruction and discontinuity of the duodenum. The cause of DA is not known. Tandler's original "solid cord" hypothesis conflicts with recent biological evidence, and is unable to account for differing DA types. In humans, a genetic etiology is supported by the association between Trisomy 21 and DA, and reports of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…Mice lacking Fgf10 or Fgfr2b have impaired development of the stomach, duodenum, cecum, and colon (Danopoulos et al, 2017; Kowalkowski et al, 2020; Lv et al, 2019). For example, genetic knockout of Fgf10 or Fgfr2b results in duodenal or colonic atresia in mice (M. L. M. Jones, Sarila, et al, 2020; Kowalkowski et al, 2020; Teague et al, 2018). Examination of the colonic epithelium in Fgfr2b −/− mice showed increased apoptosis but normal levels of proliferation.…”
Section: Selected Topics In Genetics Development Regeneration and Dis...mentioning
confidence: 99%
“…Mice lacking Fgf10 or Fgfr2b have impaired development of the stomach, duodenum, cecum, and colon (Danopoulos et al, 2017; Kowalkowski et al, 2020; Lv et al, 2019). For example, genetic knockout of Fgf10 or Fgfr2b results in duodenal or colonic atresia in mice (M. L. M. Jones, Sarila, et al, 2020; Kowalkowski et al, 2020; Teague et al, 2018). Examination of the colonic epithelium in Fgfr2b −/− mice showed increased apoptosis but normal levels of proliferation.…”
Section: Selected Topics In Genetics Development Regeneration and Dis...mentioning
confidence: 99%
“…In addition to embryological factors, the concept of genetic factors as an etiology of CGIO has been generally accepted [ 7 , 8 ]. The Prevention Network in the United States shows that gastrointestinal malformations are often correlated with trisomy 13, 18, 21 and Turner syndrome, in which the associations between duodenal stenosis/atresia and trisomy 21, esophageal stenosis/atresia and trisomy 18 are especially prominent [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…[ 5 , 6 ] The most recent research suggested that local or tissue-specific mutation in Fgf10 and Fgfr2b might represent current science's best key to unlocking this mystery. [ 7 ] However, our patient did not have a chromosome check or cDNA sequencing analysis due to economic conditions. Approximately 50% of infants with DA will have polyhydramnios due to the inability to absorb amniotic fluid.…”
Section: Discussionmentioning
confidence: 99%